V1b Receptor Antagonist SSR149415 and Naltrexone Synergistically Decrease Excessive Alcohol Drinking in Male and Female Mice. (28th November 2017) - Zhou, Yan; Rubinstein, Marcelo; Low, Malcolm J.; Kreek, Mary Jeanne
Abstract : Background: A recent clinical trial found that pharmacological blockade of V1b receptors reduces alcohol relapse in alcohol‐dependent patients. SSR149415 is a selective V1b receptor antagonist that has potential for development as an alcohol dependency treatment. In this study, we investigated whether SSR149415 alone or in combination with the mu‐opioid receptor (MOP‐r) antagonist naltrexone (NTN) would alter excessive alcohol drinking in mice. Methods: Both sexes of C57BL/6J (B6) mice were subjected to a chronic intermittent access (IA) drinking paradigm (2‐bottle choice, 24‐hour access every other day) for 3 weeks. Sucrose and saccharin drinking were used as controls for alcohol‐specific drug effects. Neuronal proopiomelanocortin (POMC) enhancer (nPE) knockout mice with hypothalamic‐specific loss of POMC (including beta‐endorphin, the main endogenous ligand of MOP‐r) were used as a genetic control for the effects of NTN. Results: Acute administration of SSR149415 (1 to 30 mg/kg) reduced alcohol intake and preference in a dose‐dependent manner in both male and female B6 mice after IA. To investigate potential synergistic effects between NTN and SSR149415, we tested 6 different combination doses of SSR149415 and NTN, and found that a combination of SSR149415 (3 mg/kg) and NTN (1 mg/kg) reduced alcohol intake profoundly at doses lower than the individual effective doses in both sexes of B6 mice. We confirmed the effect of SSR149415 on reducing alcohol intake in nPE−/− male mice, consistent with independent mechanisms by which SSR149415 and NTN decrease alcohol drinking. Conclusions: The combination of V1b antagonist SSR149415 with NTN at individual subthreshold doses shows potential in alcoholism treatment, possibly with less adverse effects. Abstract : Pharmacological blockade of V1b receptors reduces alcohol relapse in alcohol‐dependent patients. We tested combination doses of selective V1b antagonist SSR149415 and naltrexone (NTN) and found that combinations of the two human compounds reduced alcohol intake profoundly at doses lower than individual effective doses in both sexes of mice. The combination of SSR149415 with NTN shows potential in alcoholism treatment, possibly with less adverse‐effect. Figure shows dose responses of SSR149415 with NTN on reducing excessive alcohol intake (A) and preference (B).